When anxiety grows with knowledge: The role of the natural number bias - Van Hoof, Jo; Halme, Hilma; Hannula-Sormunen, Minna; McMullen, Jake (Leibniz Institute for Psychology (ZPID), 2026)
An important source for the difficulties students face with fractions is the natural number bias (NNB), which refers to the phenomenon of applying natural number properties in fraction tasks, even when this is inappropriate (e.g., 1/4+1/3 = 2/7). The present longitudinal study investigates whether this misconception is related to the development of mathematics state anxiety in the domain of fractions. The results indicated that, when a group of students with a clear NNB profile (n = 38) improved their fraction arithmetic understanding they showed an increase in state anxiety measured after the fraction arithmetic task. These results complement previous research by showing that a clear misconception, namely the natural number bias, might influence the development of students’ fraction state anxiety. Importantly, the increase in fraction state anxiety in the low-performing NNB group is not a characteristic of low performing students in general, as a significant decrease in fraction state anxiety was found in low-performing students without signs of the NNB (n = 37). The study highlights the importance of looking at different subgroups of students, as different developmental patterns can be found within qualitatively different groups of students.